PENGARUH PEMBERIAN KOMBINASI EKSTRAK BUAH MENGKUDU (Morinda citrifolia L.) DAN KUNYIT (Curcuma longa) TERHADAP HISTOPATOLOGI GINJAL TIKUS WISTAR YANG DIINDUKSI ALLOXAN - Pelastri Rahayu; Retno Hestiningsih; Martini Martini; Dwi Sutiningsih (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
The prevalence of DM in Riskesdas in 2018 according to the Perkeni consensus in 2015 is higher than according to the Perkeni consensus in 2011, the prevalence was10.9%. The disease can develop into diabetes nephropathy, Increased prevalence of diabetic nephropathy directly proportional with an increase in diabetes prevalence. Diabetic nephropathy is a microvascular complication in diabetics that develops around 30% in patients with type I DM and about 40% in patients with type II DM. Turmeric extract has antioxidant and anti-inflammatory effects to prevent the bad development of diabetes nephropathy. This study looked at the effect of giving a combination of noni and turmeric extract on histopathology of alloxan-induced renal rats. A total of 25 mice were divided into 5 treatment groups, namely the PI group (250 mg / kgBB extract dose), PII group (500 mg / kgBB extract dose), PIII group (750 mg / kgBB extract dose), positive control group (glibenklamid) and negative control group (without extract and glibenklamid). The study used Post Test Only Group. The highest percentage decrease in blood glucose in the PI group was 56.11% and the lowest decrease in the PIII group was 24.12% with p = 0.012. The results of the study were not based on the number of extract doses. The measurement results of rat body weight and glomerular diameter were not affected by blood glucose level with p = 0.700 for body weight and p = 0.187 for glomerular measurement results.